A Case of Acute Psychosis in an Adolescent Male. (30th March 2014) - Babar, Ghufran; Alemzadeh, Ramin
Abstract : Primary hyperparathyroidism (PHPT) is a disorder of calcium homeostasis. We report the case of a 17-year-old adolescent male, who presented with an acute psychosis coinciding with severe hypercalcemia and markedly elevated intact parathyroid hormone (iPTH) level and low vitamin D level. A Sestamibi scan showed a positive signal inferior to the left lobe of the thyroid gland. He had only a partial response to the initial medical and psychiatric management. The enlarged parathyroid gland was resected surgically and postoperatively serum calcium and iPTH levels normalized. The histopathology was compatible with a benign adenoma. Patient's acute psychotic symptoms resolved gradually after surgery; however he remained under psychiatric care for the behavioral issues for about 6 months after surgery. While psychosis is a rare clinical manifestation of hypercalcemia secondary to PHPT in pediatric population, it should be considered as a clinical clue in an otherwise asymptomatic pediatric patient.